Clinical Observation on Effect of Acupuncture Needling Sensation (DE-QI) Strength in Pain Management - Quek, Khai Sheng (2015)
Objectives: This study aspires to observe the relationship between the strength of needling sensation or De-Qi sensation and its efficacy in pain management, as well as to explore the role of needling sensation in acupuncture treatment. Methods: In terms of collecting clinical examples to support the research, participants were required to meet the diagnostic criteria and exclusion criteria. This research had selected a total of 60 volunteered and eligible participants, using double-blinded method to classify the participants into weak De-Qi group (control group), moderate De-Qi group, and strong De-Qi group. The acupoints were selected based on the location of pain, which is known as A-Shi point. After inserting the needle into participant’s acupoint, stimulate the needling sensation of participants by lifting and thrusting method. Then, the acupuncturist applied a relatively uniform “Green Dragon Swaying its Tail” manipulation for 30 seconds, the intensity and properties of needling sensation is being recorded immediately. The needle was then taken out immediately. The whole treatment takes less than 20 minutes and it is a single visit treatment. This research has been using numeric pain scale rating (NRPS) to evaluate the pain intensity; using Massachusetts general hospital acupuncture sensation scale (MASS) to evaluate the needling sensation of participants; using the standard of diagnosis and therapeutic effect of TCM diseases and syndromes to evaluate the clinical therapeutic effect. Results: (1) The post-treatment NPRS score of three different groups shows significant difference when compared to their pre-treatment NPRS score within their group respectively. (2) The post-treatment NPRS score among three different groups of participants have no statistical difference (P>0.05). (3) The average percentage of pain score reduction for control group (weak needling sensation) is 45.61% and its total effectiveness rate is 73.33%. (4) The average percentage of pain score reduction for moderate needling sensation group is 48.12% and its total effectiveness rate is 70.00%. (5) The average percentage of pain score reduction for strong needling sensation group is 45.79% and its total effectiveness rate is 73.33%. (6) Post-treatment NPRS score of acute pain syndrome in strong needling sensation group shows significant differences (P<0.05) compared to chronic pain syndrome. Conclusion: In conclusion, the strength of needling sensation (De-Qi) does not have positive correlation to the analgesic effect of acupuncture. However, the total effectiveness rate of those 3 groups have achieved 70% and even higher. This indicates that De-Qi is one of the important factors to achieve good curative effect. Besides, the results also shows that stronger needling sensation has good curative effect towards acute pain syndrome.